Plasmonic nanostructures and film crystallization in perovskite solar cells - Saliba, M (2014)
The aim of this thesis is to develop a deeper understanding and the technology in the nascent field of solid-state organic-inorganic perovskite solar cells. In recent years, perovskite materials have emerged as a low-cost, thin-film technology with efficiencies exceeding 16% challenging the quasi-paradigm that high efficiency photovoltaics must come at high costs. This thesis investigates perovskite solar cells in more detail with a focus on incorporating plasmonic nanostructures and perovskite film formation. Chapter 1 motivates the present work further followed by Chapter 2 which offers a brief background for solar cell fabrication and characterisation, perovskites in general, perovskite solar cells in specific, and plasmonics. Chapter 3 presents the field of plasmonics including simulation methods for various core-shell nanostructures such as gold-silica and silver-titania nanoparticles. The following Chapters 4 and 5 analyze plasmonic core-shell metal-dielectric nanoparticles embedded in perovskite solar cells. It is shown that using gold@silica or silver@titania NPs results in enhanced photocurrent and thus increased efficiency. After photoluminescence studies, this effect was attributed to an unexpected phenomenon in solar cells in which a lowered exciton binding energy generates a higher fraction of free charge. Embedding thermally unstable silver NPs required a low-temperature fabrication method which would not melt the Ag NPs. This work offers a new general direction for temperature sensitive elements. In Chapters 6 and 7, perovskite film formation is studied. Chapter 6 shows the existence of a previously unknown crystalline precursor state and an improved surface coverage by introducing a ramped annealing procedure. Based on this, Chapter 7 investigates different perovskite annealing protocols. The main finding was that an additional 130°C flash annealing step changed the film crystallinity dramatically and yielded a higher orientation of the perovskite crystals. The according solar cells showed an increased photocurrent attributed to a decrease in charge carrier recombination at the grain boundaries. Chapter 8 presents on-going work showing noteworthy first results for silica scaffolds, and layered, 2D perovskite structures for application in solar cells.